Control of robots with nonlinear phenomena in the joints - Azenha, Abílio (1996)
This paper develops the analysis of robots with dynamic phenomena at the joints such as friction, backlash and flexibility. The study adopts the describing function (DF) calculation and a decoupling procedure. The DF's are evaluated by decoupling the link inertias and ignoring the centrifugal, Coriolis and gravitational effects. The controllers studied are the first order model and the second order model variable structure controllers (FOM-VSC and SOM-VSC). Results show that the best case in terms of performance is the robot system with nonlinear friction, while the worst is the manipulator system with backlash.